The Future of Coral Reefs Subject to Rapid Climate Change: Lessons from Natural Extreme Environments - Peter J. Mumby (Frontiers Research Topics, 2019)
Examination of corals and reef-associated organisms which endure in extreme coral reef environments is challenging our understanding of the conditions that organisms can survive under. By studying individuals naturally adapted to unfavorable conditions, we begin to better understand the important traits required to survive rapid environmental and climate change. This Research Topic, comprising reviews, and original research articles, demonstrates the current state of knowledge regarding the diversity of extreme coral habitats, the species that have been studied, and the knowledge to-date on the mechanisms, traits and trade-offs that have facilitated survival.